HUBUNGAN KEAMANAN LINGKUNGAN TERHADAP RESIKO JATUH PADA LANSIA - Melinia, Rizky; Wijaya, Leni (Jurnal Kesehatan dan Pembangunan, 2025)
The increase in age in the elderly tends to be accompanied by a decrease in the body's functional capabilities which have an impact on the body's immune system. Changes in the musculoskeletal system will cause the risk to fall in the elderly. The degenerative aging process caused by increasing age, will have an impact on physical, cognitive, emotional, social, and sexual changes. The purpose of this study is to see the relationship between environmental safety and the risk of falling on the elderly in the Palembang Harapan Kita Elderly Social Home 2025. The research method uses a quantitative analytical method with a cross sectional approach. The population in this study is all elderly people in the Harapan Kita Elderly Social Home Palembang. Using purposive sampling that is in accordance with the inclusion and exclusion criteria with a sample of 35 respondents. The results of the study were obtained in frequencyattribution, most of the respondents stated that the orphanage environment was at risk as many as 24 respondents (68.6%), most of the respondents were not at risk of falling as many as 13 respondents (37.1%). The results of the statistical test found that there was a relationship between environmental safety and the risk of falling on the elderly at the Palembang Harapan Kita Elderly Social Home in 2025 with p.value = 0.012. Suggestion It is hoped that it can improve the safety of the environment in the orphanage environment by improving the facilities in the orphanage environment so that it provides convenience for the elderly in carrying out daily activities and can minimize the risk of falling on the elderly.